2015
DOI: 10.1186/s12879-015-0864-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anthelmintic treatment intervention on malaria infection and anaemia in school and preschool children in Magu district, Tanzania: an open label randomised intervention trial

Abstract: BackgroundSome studies have suggested that helminth infections increase the risk of malaria infection and are associated with increased number of malaria attacks and anaemia. Thus interventions to control helminth infections may have an impact on incidence of clinical malaria and anaemia. The current study assessed the impact of two anthelmintic treatment approaches on malaria infection and on anaemia in school and pre-school children in Magu district, Tanzania.MethodsA total of 765 children were enrolled into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
1
16
1
Order By: Relevance
“…163 Finally, data suggest that deworming may have beneficial effects on co-infections such as HIV, 164,165 and further research is needed to determine the impact of anthelmintic treatment on malaria. 166,167 OUTSTANDING RESEARCH One of the principal bottlenecks for adequate individual diagnosis and management, as well as public health control of STH, has been insufficient investment in research and development of diagnostic tools and treatment options. This is especially true for Strongyloides, which has been called the most neglected of NTDs.…”
Section: Controversiesmentioning
confidence: 99%
“…163 Finally, data suggest that deworming may have beneficial effects on co-infections such as HIV, 164,165 and further research is needed to determine the impact of anthelmintic treatment on malaria. 166,167 OUTSTANDING RESEARCH One of the principal bottlenecks for adequate individual diagnosis and management, as well as public health control of STH, has been insufficient investment in research and development of diagnostic tools and treatment options. This is especially true for Strongyloides, which has been called the most neglected of NTDs.…”
Section: Controversiesmentioning
confidence: 99%
“…Tanzania is located at the mid-eastern part of sub-Saharan Africa south to Kenya and Uganda and north to Mozambique. In Tanzania, malaria prevalence was reported to be variable according to geographical regions and ecosystem [ 3 - 6 ]. In a national survey performed in 2011-2012 in Tanzania, high malaria prevalence was reported in regions adjacent to Lake Victoria (Geita; 20.7% and Mara; 14.4%) and Lake Tanganyika (Kigoma; 9.9%) [ 3 ].…”
mentioning
confidence: 99%
“…In Kilosa district, central Tanzania, the malaria prevalence of schoolchildren was as low as 4.5% [ 4 ]. However, around the lakeside areas of Lake Victoria malaria prevalence has been reported to be quite high [ 5 , 6 ]. For example, in another side of Lake Victoria, Magu district, north-western Tanzania, a high malaria prevalence of 29.8% [ 5 ] to 44.9% [ 6 ] was reported among school and pre-schoolchildren.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An opposing study found more serious hepato-splenomegaly in chronic malaria exposed augmented by concomitant S. mansoni infection and demonstrated pro-inflammatory mechanisms behind the additive effect [35] . Nevertheless, the recovery from organomegaly after PZQ in the current study cannot be explained by concomitant malaria-infection, as Plasmodium falciparum is refractive to PZQ treatment [36] . Distinguishing between organomegaly caused by malaria and schistosomiasis is a problem due to the geographic and seasonal overlap of the two diseases [37] .…”
Section: Discussionmentioning
confidence: 57%